Analysis of structures of rubber-filler systems with combined scattering methods - Takenaka, Mikihito (Polymer journal, 2013)
This review presents an analysis of the hierarchical structures formed in rubber-filler systems by using combined scattering methods. The combined scattering methods utilize various scattering methods and are powerful tools for the quantitative characterization of hierarchical structures over a wide range of length scales, ranging from nanometers to micrometers. Scattering theories for the analysis of the experimental scattering functions and their applications are described. Rubber-filler systems have been widely used in industry. Fillers are not dispersed homogeneously and often form hierarchical structures in rubber matrices over a wide range of length scale from nanometer to micron meters, such as primary particles, aggregates and agglomerates. The combined scattering methods are powerful tools to characterize the structures quantitatively.